Brief education supported psychological treatment for adolescent borderline personality disorder: the BEST feasibility RCT - Jon Wilson; Brioney Gee; Nicola Martin; Sarah Maxwell; Jamie Murdoch; Tim Clarke; Allan Clark; David Turner; Caitlin Notley; Thando Katangwe; Peter B Jones; Peter Fonagy (NIHR Journals Library, 2022)
Background: Borderline personality disorder is a severe mental health condition characterised by a pattern of emotional instability, interpersonal dysfunction, disturbed self-image and impulsive behaviour, including self-harm. Symptoms of borderline personality disorder typically emerge during adolescence. Although there is compelling evidence in support of early intervention for borderline personality disorder, current evidence-based interventions are resource intensive, with the result that few young people access timely treatment. Therefore, there is an urgent need for accessible interventions to facilitate early intervention for adolescents with borderline personality disorder symptoms. Objectives: The first objective was to adapt a brief psychological treatment for adolescent borderline personality disorder that had previously been delivered within secondary mental health services for co-delivery within schools and colleges. The second objective was to assess the feasibility of evaluating the clinical effectiveness and cost-effectiveness of this intervention in a future randomised controlled trial. Design: We first conducted a rapid evidence synthesis of barriers to and facilitators of the implementation of indicated mental health interventions for adolescents within educational settings and piloted the prototype intervention with three schools/colleges. Based on the findings of the evidence synthesis and pilot, we refined the intervention and study procedures in preparation for a feasibility randomised controlled trial. The feasibility randomised controlled trial involved 12 schools and colleges, whose pastoral staff members received training to deliver the intervention alongside a mental health practitioner. Participants were randomised in a 1 : 1 ratio to receive either the BEST (Brief Education Supported Treatment) intervention plus treatment as usual or treatment as usual alone. Participants were assessed pre randomisation (baseline) and at 12 and 24 weeks post randomisation. Mixed-methods process data were collected to understand how the intervention was implemented, to assess acceptability and to monitor contamination of the control arm. Participants: Young people eligible to participate were aged 13-18 years, reported symptoms of borderline personality disorder above an established threshold and had a history of repeated self-harm. Results: The intervention was refined based on findings of the rapid evidence synthesis, which included 50 studies, feedback from staff participants in the pilot and analysis of session recordings. In the feasibility randomised controlled trial, we randomised 32 participants prior to the premature closure of recruitment. The rate of recruitment was slower than anticipated but would probably have narrowly surpassed our progression criterion over the full recruitment window. Participant retention was high (89.5% at 12 weeks and 73.7% at 24 weeks) and the performance of the proposed outcome measures was satisfactory. We did not find any evidence that participants allocated to the treatment-as-usual arm received the BEST intervention or its components. Fidelity of intervention delivery was high (93.5% of recordings rated as adherent) and the intervention was viewed as offering benefits for individual participants, practitioners involved in co-delivery and the wider school/college. Limitations: The feasibility randomised controlled trial was disrupted by the closure of schools and colleges in response to the COVID-19 pandemic. This reduced the window for participant recruitment and limited the data that could be collected. Conclusions: The refined BEST intervention was able to be delivered successfully within schools and colleges and was found to be acceptable to staff and young people. The findings provide support for continuing this programme of research and would inform the design of a future trial. Trial registration: This trial is registered as ISRCTN16862589. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme and will be published in full in Health and Social Care Delivery Research; Vol. 10, No. 37. See the NIHR Journals Library website for further project information.